Informacja publiczna w działalności uczelni publicznych w świetle orzecznictwa sądów administracyjnych - Jung, Jakub (Kwartalnik Prawa Publicznego, 2012)
The right to public information is the basic element of the democratic state of law, thus it plays an essential role in the modern state, an inseparable element of which is the information society. The information generated by the public authorities in the broad sense of the term is also of particular interest to civil society. Therefore, the idea of the openness of administration in the broad sense of the term, which has been given the status of constitutional principle in Poland, has been researched into within this study. Public universities, as entities that carry out public tasks, are an important element of the common system of education. Public universities’ activities are financed from the state budget, thus the transparency of the activities undertaken by the universities became the starting point in this publication. In order to meet the predetermined objective the analysis of acts and the jurisdiction of administrative courts was carried out. The above methodology allows to try to discuss the particular types of information accumulated, processed and communicated by public universities. Consequently, the presented observations de lege lata and de lege ferenda should lead to conclusions concerning fundamental issues that arise while determining the group of entities, to whom the information is available, the circle of persons who have the right of access to it, and the scope in question of the matter discussed.